Disparities in cause-specific mortality by health insurance type and premium: evidence from Korean NHIS-HEALS cohort study, 2002-2019 - Ye-Seul Kim; Joungyoun Kim; Yonghoon Kim; Hee-Taik Kang (BMC, 2024)
Abstract Background Although one's socioeconomic status affects health outcomes, limited research explored how South Korea's National Health Insurance (NHI) system affects mortality rates. This study investigated whether health insurance type and insurance premiums are associated with mortality. Methods Based on the National Health Insurance Service-Health Screening cohort, 246,172 men and 206,534 women aged ≥ 40 years at baseline (2002-2003) were included and followed until 2019. Health insurance type was categorized as employee-insured (EI) or self-employed-insured (SI). To define low, medium, and high economic status groups, we used insurance premiums at baseline. Death was determined using the date and cause of death included in the cohort. Cox proportional hazard models were used to analyze the association between insurance factors and the overall and cause-specific mortality. Results The SI group had a significantly higher risk of overall death compared to the EI group (adjusted hazard ratio (HR) [95% confidence interval]: 1.13 [1.10-1.15] for men and 1.18 [1.15-1.22] for women), after adjusting for various factors. This trend extended to death from the five major causes of death in South Korea (cancer, cardiovascular disease, cerebrovascular disease, pneumonia, and intentional self-harm) and from external causes, with a higher risk of death in the SI group (vs. the EI group). Further analysis stratified by economic status revealed that individuals with lower economic status faced higher risk of overall death and cause-specific mortality in both sexes, compared to those with high economic status for both health insurance types. Conclusion This nationwide study found that the SI group and those with lower economic status faced higher risk of overall mortality and death from the five major causes in South Korea. These findings highlight the potential disparities in health outcomes within the NHI system. To address these gaps, strategies should target risk factors for death at the individual level and governments should incorporate such strategies into public health policy development at the population level. Trial registration This study was approved by the Institutional Review Board of Chungbuk National University Hospital (CBNUH-202211-HR-0236) and adhered to the principles of the Declaration of Helsinki (1975).